OPTIMIZATION OF COMMUNITY-BASED EQUIVALENCY EDUCATION PROGRAMS FOR FOSTERED CHILDREN IN CLASS 1 CHILDREN'S SPECIAL DEVELOPMENT INSTITUTION TANGERANG - Khatimah, Husnul; Muhammad, Ali (PT Altin Riset Publishing, 2025)
The purpose of this research is to be able to describe the factors that influence the implementation of the education program at LPKA. The theory used in this study uses the theory of education with a qualitative descriptive research method which aims to be able to describe cases, problems and realities widely and deeply. The techniques used in data collection are observation and interviews. The results showed that the crucial aspect in education theory shows the nature of students where there is a low sense of desire of students in learning, so that the education program cannot run optimally. The conclusion of this study is that the factors that can influence the education program to be optimal are running well, but there are factors of the nature of students that are not implemented properly so that the implementation of learning by educators is hampered in its implementation.